Durability behavior of asphalt mixtures in regard to material properties and gradation type - Ji, Tonggeng; Hao, Peiwen; She, Hongwei; Yang, Kai; Li, Hongxiang; Wang, Dong; Kang, Rui; Liu, Jingwen (Frontiers in Materials, 2023)
The main objective of this study was to compare SMA, LSA, SAC, SUPERPAVE to dense graded mixture in terms of their resistance to rutting, moisture damage, and low temperature cracking, water permeability. And studied on effect of modified asphalt on asphalt mixture performance, The results indicated that the gradation type has a significant effect on rutting resistance, SMA20, SAC20 and LSA30 have low rutting potential than AC20, SAC20 have larger stripping ratio, AC13 have low stripping ratio, SMA shows the largest failure strain, while SAC shows the smallest failure strain and SUPERPAVE is between the SAC and SMA. SAC20 shows the greatest the permeability coefficient, followed by SMA20, AC20 and SUPER20 comes in last, Nominal maximum aggregate sizes have significantly effect on resistance to permanent deformation, resistance to cracking at low temperature ,moisture susceptibility and permeability, SBS modified asphalt can improves significantly asphalt mixture properties.